The vineyard : a novel - Dueñas, María, 1964- (Atria Books, 2017)
"New York Times bestselling author Maria Duenas returns with The Vineyard, a magnificent story of ambition, heartbreak, and desire set in the 1860s Mexico, Cuba, and Spain--perfect for fans of Kate Morton and Kristin Hannah. Mauro Larrea's fortune, the result of years of hardship and toil, comes crashing down on the heels of a calamitous event. Swamped by debt and uncertainty, he gambles the last of his money in a daring play that wins him an abandoned house and a vineyard an ocean away. Mauro travels to Andalusia de Jerez in Spain with every intention of selling the property and returning to Mexico. That is, until he meets the unsettling Soledad Montalvo, the widow of a London wine merchant who bursts into his life unannounced, determined to protect herfamily's legacy. Before long, Mauro finds himself immersed in the rich culture of the sherry trade. As his feelings for Soledad ripen into a consuming passion, he seeks to restore the vineyard to its former glory, propelling himself toward a future thathe never could have imagined. From the turbulent young Mexican republic to flourishing Havana to the fertile vineyards of Jerez in the second half of the nineteenth century, when the wine trade with England transformed the Andalusian city, Maria Duenas'new novel takes place on both sides of the Atlantic, the New World and the Old. This story of family intrigue vividly conjures the noise and grit of silver mines, the sophistication of the Mexican capital, and the earthier lure of ancient vineyards and magnificent cities whose splendor has faded. Here is a story of courage in the face of adversity and of a destiny forever altered by the force of passion"--